Sustainable Development of the Innovation Ecosystem from the Perspective of T-O-V - Ruixue Yan; Jianlin Lv; Qingshi Meng (Complexity)
The innovation ecosystem is a dynamic network system of competition and cooperation between entities and enterprises as the core in order to achieve value cocreation. Technology provides growth power for the innovation ecosystem, organization provides management support for the innovation ecosystem, and value has a guiding effect on the innovation ecosystem. From the perspective of technology-organization-value to study the sustainable development of the innovation ecosystem, build a system dynamics model, take the automotive industry innovation ecosystem as a research case, and find that technological elements have the most significant role in promoting innovation performance and organizational elements have a role in promoting economic benefits. Most notably, the coordinated adjustment of technological elements, organizational elements, and value elements is conducive to improving the innovation performance and economic benefits of the innovation ecosystem, and corresponding management measures are proposed from the dimensions of technology, organization, and value, which further promotes the sustainable development of the innovation ecosystem.